Multiregion deep sequencing of hepatitis C virus: An improved approach for genetic relatedness studies - Goncalves Rossi, Livia Maria [UNESP]; Escobar-Gutierrez, Alejandro; Rahal, Paula [UNESP] (Elsevier B.V., 2016)
Hepatitis C virus (HCV) is a major public health problem that affects more than 180 million people worldwide. Identification of HCV transmission networks is of critical importance for disease control. HCV related cases are often difficult to identify due to the characteristic long incubation period and lack of symptoms during the acute phase of the disease, making it challenging to link related cases to a common source of infection. Additionally, HCV transmission chains are difficult to trace back since viral variants from epidemiologically linked cases are genetically related but rarely identical. Genetic relatedness studies primarily rely on information obtained fromthe rapidly evolving HCV hypervariable region 1 (HVR1). However, in some instances, the rapid divergence of this region can lead to loss of genetic links between related isolates, which represents an important challenge for outbreak investigations and genetic relatedness studies. Sequencing of multiple and longer sub-genomic regions has been proposed as an alternative to overcome the limitations imposed by the rapid molecular evolution of the HCV HVR1. Additionally, conventional molecular approaches required to characterize the HCV intra-host genetic variation are laborious, time-consuming, and expensive while providing limited information about the composition of the viral population. Next generation sequencing (NGS) approaches enormously facilitate the characterization of the HCV intra-host population by detecting rare variants at much lower frequencies. Thus, NGS approaches using multiple sub-genomic regions should improve the characterization of the HCV intrahost population. Here, we explore the usefulness of multiregion sequencing using a NGS platform for genetic relatedness studies among HCV cases. (C) 2015 Elsevier B.V. All rights reserved.
Keywords: Hepatitis C virus; Next generation sequencing; Outbreak; Multiregion; Genetic relatedness